CDSS and DSS: shared roots and divergent paths. (18th August 2020) - Crowley, Jill; Heavin, Ciara; Keenan, Peter; Power, Daniel
ABSTRACT: Clinical Decision Support Systems (CDSS) is an important research area. With an increase in focus on digital health globally, the area of CDSS continues to grow. However, based on our preliminary literature investigation evidence suggests that it is difficult to determine the scope and ambitions of CDSS research. This is primarily due to the substantial spread of relevant literature in interdisciplinary domains. This work-in-progress article investigates the CDSS literature to establish how the area has evolved. Our aim is to understand if the "traditional" mainstream DSS research agenda has influenced CDSS research. The initial literature search of Scopus and Google Scholar and bibliometric analysis provides justification for further interrogation of the CDSS literature. From our analysis, CDSS research is wide and varied. It appears there has been minimal cross fertilisation between CDSS research and the mainstream DSS research domain, with the exception of a few high profile DSS articles.